Random Operators and Stochastic Equations (De Gruyter, 1993)
ROSE is devoted to the theory of random operators and stochastic analysis. Contributions on theoretical aspects, as well as on physical and technical applications are considered for publication. The scope includes the general theory of linear random operators, the theory of random matrices, chaos in classical and quantum mechanics, stochastic differential equations, Brownian motion theory and many other topics.